Markers of Hypoxia and Metabolism Correlate With Cell Differentiation in Retina and Lens Development - Gardiner, Tom A.; Branagh, Tiarnan; Tipping, Nuala; McDonald, Denise M. (Frontiers in Ophthalmology, 2022)
Recent studies have provided novel insights of co-development of the neural and vascular elements of the retina. Knowledge of these relationships are crucial to understand the impact of therapeutic measures in Retinopathy of Prematurity (ROP). ROP is imposed by therapeutic oxygen upon immature retinal blood vessels and neural cells causing delayed development and vascular regression. However, the impact of hyperoxia on developing retinal neurons is less understood because some aspects of normal development remain unknown. The metabolic changes during differentiation of retinal progenitor cells to functional neurons is one such aspect. We correlated immunomarkers of hypoxia with markers of metabolic change in developing retinal neurons during the early postnatal period in mice. The same marker proteins were studied in secondary lens fiber differentiation at postnatal day-3 (P3). Nuclear localization of the oxygen-sensitive subunits of hypoxia inducible factor, HIF-1α and HIF-2α was correlated with increasing mitochondrial content in differentiating neurons. Nuclear HIF was also correlated with AMP-dependent protein kinase (AMPK), and the AMPK phosphorylation target PPAR-gamma coactivator-1alpha (PGC-1α), the principal regulator of mitochondrial biogenesis. Expression of AMPK, PGC1α and HIF-2α in secondary fiber differentiation was visible in each profile of the lens equator. Strong nuclear localization for all markers was present at the onset of secondary fiber differentiation, and reflected changes in size, mitochondrial content, and metabolism. We speculate that the ‘physiological hypoxia’ that drives retinal vascular development is cell-specific and reliant upon neuronal differentiation and mitochondrial biogenesis. We suggest that the onset of differentiation increases energy consumption that is detected by AMPK. In turn AMPK increases mitochondrial biogenesis via PGC-1α. Mitochondrial oxygen consumption may then create intracellular hypoxia that activates HIF. This progression is congruent with the expression of these markers in secondary lens fiber differentiation and nuclear localization of HIF-2α. Nuclear localization of HIF-1α and HIF-2α in the postnatal retina is less defined than in the lens as it may involve the remnant of HIF expression from the embryonic period that is sustained and increased by intracellular hypoxia caused by increasing mitochondrial oxygen consumption. This the first report of the involvement of HIF-2α, AMPK and PGC-1α in lens development.